Uji Aktivitas Antibakteri Ekstrak Etanol Daun Sirih Cina (Peperomia pellucida (L.) Kunth). Terhadap Bakteri Propionibacterium acnes, Staphylococcus epidermidis dan Staphylococcus aureus - Hermawan Purba; Geby Hilleri Damanik (Program Studi S1 Farmasi, STIKES Senior, Medan, 2026)
Pathogenic bacteria have negative impacts if exposed to the human body for a certain period of time. It is necessary to inhibit bacterial growth from natural materials because they generally have non-toxic, environmentally friendly, and biodegradable properties. This study used Chinese betel leaf extract (Peperomia pellucida (L.) Kunth) as an antibacterial material against Propionibacterium acnes, Staphylococcus epidermidis and Staphylococcus aureus. The results of the phytochemical screening analysis showed that there were secondary metabolites in the extract and simplicia such as tannins, alkaloids, and flavonoids. The antibacterial test pad with the largest concentration variation has a strong and very strong category on the three types of bacteria, namely against Staphylococcus epidermidis (diameter 19.9 mm) at a concentration of 5%, Staphylococcus aureus (diameter 22.92 mm) at a concentration of 7%, Propionibacterium acnes. (diameter 19.63 mm) at a concentration of 7%.